Management of abdominal ectopic pregnancy: case series - Miranda Flores, Alan Francis (2024)
Background: Abdominal ectopic pregnancy accounts for 1-1.4% of ectopicpregnancies and is associated with a high maternal mortality rate mainly due tomassive hemorrhage. Objective: To describe the experience in the managementof abdominal ectopic pregnancy at the Instituto Nacional Materno Perinatal, Lima,Peru. Materials and methods: Descriptive and retrospective study. The studypopulation was patients with a diagnosis of abdominal ectopic pregnancy during theperiod 2021-2023. Data was obtained from the review of medical records. Statisticalanalysis was processed in the SPSS 24 software. Results: Seven cases of abdominalectopic pregnancy were recorded. The mean age was 31.3 years; 57.1% of the caseshad no risk factors. The mean gestational age was 9 weeks. The majority presentedabdominal pain as the only symptom (71.4%). Preoperative diagnosis occurred in42.9% of the cases. Hemoperitoneum was present in 57.1%. The most frequentsite of implantation was the broad ligament (42.9%). Treatment was surgical in allcases. One case presented hemoperitoneum as a postoperative complication dueto bleeding of the placental bed. Conclusions: Surgery continues to be the treatmentof abdominal ectopic pregnancy. There is controversy regarding the removal of theplacenta in advanced gestational ages.